Distributed representations of temporal stimulus associations across regular-firing and fast-spiking neurons in rat medial prefrontal cortex - Xing, Bohan (J Neurophysiol, 2020)
The prefrontal cortex has been implicated in various cognitive processes, including working memory, executive control, decision making, and relational learning. One core computational requirement underlying all these processes is the integration of information across time. When rodents and rabbits associate two temporally discontiguous stimuli, some neurons in the medial prefrontal cortex (mPFC) change firing rates in response to the preceding stimulus and sustain the firing rate during the subsequent temporal interval. These firing patterns are thought to serve as a mechanism to buffer the previously presented stimuli and signal the upcoming stimuli; however, how these critical properties are distributed across different neuron types remains unknown. We investigated the firing selectivity of regular-firing, burst-firing, and fast-spiking neurons in the prelimbic region of the mPFC while rats associated two neutral conditioned stimuli (CS) with one aversive stimulus (US). Analyses of firing patterns of individual neurons and neuron ensembles revealed that regular-firing neurons maintained rich information about CS identity and CS-US contingency during intervals separating the CS and US. Moreover, they further strengthened the latter selectivity with repeated conditioning sessions over a month. The selectivity of burst-firing neurons for both stimulus features was weaker than that of regular-firing neurons, indicating the difference in task engagement between two subpopulations of putative excitatory neurons. In contrast, putative inhibitory, fast-spiking neurons showed a stronger selectivity for CS identity than for CS-US contingency, suggesting their potential role in sensory discrimination. These results reveal a fine-scaled functional organization in the prefrontal network supporting the formation of temporal stimulus associations. NEW & NOTEWORTHY To associate stimuli that occurred separately in time, the brain needs to bridge the temporal gap by maintaining what was presented and predicting what would follow. We show that in rat medial prefrontal cortex, the former function is associated with a subpopulation of putative inhibitory neurons, whereas the latter is supported by a subpopulation of putative excitatory neurons. Our results reveal a distinct contribution of these microcircuit components to neural representations of temporal stimulus associations.